Brazilian aphidoidea. III. Sub-family Drepanosiphinae - Eastop, V. F.; Costa, Cláudio L.; Blackman, Roger L. (Pesquisa Agropecuaria Brasileira, 1993)
Keys are provided for the identification of the tribes, genera and species of Brazilian Drepanosiphinae. Host plant and distribution data are given for each species.